Patients' Perspectives on Information and Communication About Sexual and Relational Issues in Rheumatology Health Care. (13th July 2016) - Helland, Ylva; Dagfinrud, Hanne; Haugen, Mona‐Iren; Kjeken, Ingvild; Zangi, Heidi
Abstract: Introduction: Men and women with rheumatic diseases report a significantly negative impact on multiple areas of life, including sexuality. Research indicates that patients want to discuss sexual issues with health professionals (HPs) in rheumatology care but these issues are rarely addressed in consultations. Aim: The objective of the present study was to explore patients' experiences of communication with HPs about disease‐related sexual issues, their perceptions of the relevance of these issues in rheumatology care and their preferences for how these topics should be handled. Methods: A qualitative design was used and 18 semi‐structured interviews were performed, including eight women and ten men with inflammatory rheumatic joint diseases, aged 29–62 years. The interviews were recorded and transcribed verbatim. Data were analysed thematically. Results: Four main themes were derived from the interviews: (i) relevance of sexual issues; (ii) vital conditions for communication; (iii) individual preferences in mode and timing of information and communication; and (iv) benefits of information and communication. The participants expressed that, although sexual issues are relevant, necessary conditions for good communication are largely lacking. HPs' knowledge, experience and personal skills, as well as having sufficient time were essential. HPs lack of initiating sexual topics contributed to uncertainty about whether their sexual challenges were disease related and whether it was a legitimate topic to discuss in rheumatology care. Conclusion: Patients wanted HPs to possess knowledge about possible disease‐related challenges in sexual life and intimate relationships, and to facilitate communication about these aspects. There is a need to develop practice guidelines to enable HPs to integrate sexual issues as an aspect of healthcare delivery in a patient‐friendly manner. Copyright © 2016 John Wiley & Sons, Ltd.